Persisting embryonal infundibular recess masquerading as a nasal mass - Joshua, Shejoy; Sreedhar, Shyamsundar; Viswam, Vineeth; Panikar, Dilip (Asian Journal of Neurosurgery, 2018)
Persisting embryonal infundibular recess (PEIR) is a rare anomaly of the development of the posterior pituitary wherein there is a defect in the third ventricular floor. Earlier reports have found PEIR descending only up to the sella. However, this is the first case of PEIR presenting as a pulsatile nasal mass. A 35-year-old female presented to the otorhinolaryngologist with hyposmia. Diagnostic nasal endoscopy revealed a pulsatile nasal mass. Magnetic resonance imaging revealed a cystic lesion extending from the third ventricular floor to the nasal cavity. There was no associated hydrocephalus or empty sella. The case was successfully managed by the endoscopic endonasal transsphenoidal approach.
Keywords: Encephalocoele; nasal mass; persisting embryonal infundibular recess